Differential Effects of High Fat Diets on Resilience to H2O2-Induced Cell Death in Mouse Cerebral Arteries: Role for Processed Carbohydrates - Charles E. Norton; Rebecca L. Shaw; Steven S. Segal (MDPI AG, 2023)
High fat, western-style diets increase vascular oxidative stress. We hypothesized that smooth muscle cells and endothelial cells adapt during the consumption of high fat diets to become more resilient to acute oxidative stress. Male C57Bl/6J mice were fed a western-style diet high in fat and processed carbohydrates (WD), a high fat diet that induces obesity (DIO), or their respective control (CD) and standard (SD) diets for 16 weeks. Posterior cerebral arteries (PCAs) were isolated and pressurized for study. During acute exposure to H2O2 (200 µM), smooth muscle cell and endothelial cell death were reduced in PCAs from WD, but not DIO mice. WD selectively attenuated mitochondrial membrane potential depolarization and vessel wall Ca2+ influx during H2O2 exposure. Selective inhibition of transient receptor potential (TRP) V4 or TRPC3 channels reduced smooth muscle cell and endothelial cell death in concert with the vessel wall [Ca2+]i response to H2O2 for PCAs from CD mice and eliminated differences between CD and WD. Inhibiting Src kinases reduced smooth muscle cell death along with [Ca2+]i response to H2O2 only in PCAs from CD mice and eliminated differences between diets. However, Src kinase inhibition did not alter endothelial cell death. These findings indicate that consuming a WD, but not high fat alone, leads to adaptations that limit Ca2+ influx and vascular cell death during exposure to acute oxidative stress.